Rosa Calzecchi Onesti's studies on authorial variants (ACME, 2024)
In Italy, Rosa Calzecchi Onesti (1916-2011) is known and appreciated for her translations, still considered reference points, of Iliad (1950), Odyssey (1963) and Aeneid (1967); very little attention, on the other hand, has been dedicated to her philological research on the text of the Virgilian poem. Calzecchi composed her dissertation, discussed in Bologna in 1940 under the guidance of Gino Funaioli, around the thorny question of the possible presence of residual authorial variants in the text of the Aeneid. Part of the results flowed into her critical edition of the Latin text for the Istituto Editoriale Italiano in 1962, a few years before she authored the much better-known Italian translation for Einaudi. Admittedly, the hypothesis of surviving authorial variants in Virgil’s text has long been discarded by critics. Nevertheless, a closer look does provide some new insight in the history of classical studies: the question of authorial variants – in Vergil’s Aeneid as in that of other classical authors – was in fact, at the time Calzecchi worked, a hotly debated issue. In addition to that, despite her overall outdated theory, there is at least one of the criteria that she identified which can be recovered and profitably applied to those traditions in which – contrary to the case of Vergil – the presence of authorial variants is plausible or established.
Keywords: Authorial variants; Rosa Calzecchi Onesti; Vergil; Aeneid; History of classical scholarship